Unpacking SDG target 11.a: What is it about and how to measure its progress?. (April 2022) - Berisha, Erblin; Caprioli, Caterina; Cotella, Giancarlo
Highlights: The UN 2030 Agenda and its SDGs are characterised by many targets and indicators to monitor the progress achieved; Not all targets that concern the SDG11 are easy to operationalise. Similarly, the indicators put forward to measure the progress of some of these targets are rather opaque and require further detailing; In particular, multidimensional indicators are needed to operationalise the Target 11.a, concerning the quality of spatial governance and planning in a given context; A set of procedural, instrumental, and financial indicators are proposed in this concern; Regional and Local public authorities may take advantage of the proposed indicators' toolbox to reflect on what measures and initiatives they can put in place to make their action more effective. Abstract: The pivotal role that urbanisation plays in global development trajectories is clearly acknowledged by the United Nations 2030 Agenda that, among its 17 Sustainable Development Goals, explicitly argues in favour of cities and human settlements to be more inclusive, safe, resilient and sustainable (SDG11). Whereas SDG11 targets are paired with one or more indicators to monitor their achievement, in some cases this process is not straightforward. In particular, when it comes to Target 11.a Support positive economic, social and environmental links between urban, peri-urban and rural areas by strengthening national and regional development planning, the identified indicator does not seem able to grasp the complexity of national and regional governance, policy and planning. With the aim to contribute to this concern, the paper conceptually discusses the contents and implications of the SDG11 target 11.a. On this basis, it develops a multi-dimensional set of indicators to assess the quality of spatial governance and planning in a given context, and divides them into three main categories: (i) procedural indicators, (ii) instrumental indicators and (iii) financial indicators. The result of this work is a toolbox that may support decision-makers and policy-makers in assessing the quality of the efforts they put in place to make their cities and territories more sustainable as well as to reflect on what measures and initiatives could make this action more effective.